Deliberating just transition: lessons from a citizens’ jury on carbon-neutral transport - Heli Saarikoski; Suvi Huttunen; Hanna Mela (Sustainability: Science, Practice, & Policy, 2023)
AbstractClimate assemblies and other forms of deliberative mini-publics have recently gained prominence as a means to promote just climate transitions. In this article, we analyze a citizens’ jury process that addressed ways to curb greenhouse-gas emissions from car-based mobility in the Uusimaa region of Finland. The four-day citizens’ jury produced a joint statement on transport-policy measures to decrease the mileage of private cars, to promote cycling and walking, to support public transport, and to promote carbon-free fuels. One of the key discoveries for the jurors was that there are no easy fixes, like biofuels converters, to cut down transport emissions. Consequently, the jurors endorsed vehicle electrification as a future solution. They also came up with an innovative suggestion to make electric cars more affordable to people. Overall, they adopted a more positive view toward measures to promote fossil-free transport, suggesting that deliberation can increase support for environmental initiatives. However, the deliberative process did not create wide acceptance of radical climate-policy measures. The results highlight the importance of mini-public scope and design for formulating an informed citizen judgment on complex and science-intensive climate-policy questions. The Transport Jury’s focus on a set of policy measures was sufficiently narrow to produce meaningful recommendations. However, future climate-jury processes with a similar objective would benefit from more time for face-to-face expert hearings than was available for the transport jurors. A search for meta-consensus rather than consensus retained the plurality of perspectives.